Criminal Justice Contact, Stressors, and Depressive Symptoms Among Black Adults in the United States - Archibald, Paul C. (American journal of criminal justice, 2018)
Criminal justice contact—defined as lifetime arrest, parole, or incarceration is associated with higher odds of experiencing depressive symptoms. Findings from this study suggest that there is a mechanism that links family, neighborhood, and financial stressors among Black adults with criminal justice contact to depressive symptoms. Using the National Survey of American Life (NSAL), modified poisson regression analyses were used to determine the association between criminal justice contact, stressors, and depressive symptoms among a national sample of Black adults ( n = 3570). In the full model, the odds of experiencing depressive symptoms for Black adults who had criminal justice contact was reduced (PR: 1.14 to PR: 1.07). Black adults who reported experiencing family stressors (PR: 1.10, 95% CI: 1.06, 1.16), neighborhood stressors (PR: 1.09, 95% CI: 1.04, 1.13), and financial stressors (PR: 1.13, 95% CI: 1.06, 1.19) were statistically significant and higher than those who reported not experiencing any of these stressors. Stressors partially mediates the relationship between criminal justice contact and depressive symptoms (OR: 1.05, Bias-corrected 95% CI: 1.04, 1.07); causing the effect of criminal justice contact to reduce to 1.06, leaving a significant indirect effect of 1.05. The total effect is 1.93 times larger than the direct effect, and 48.3% of the total effect is due to stressors. These findings emphasize the need to further explore the family, neighborhood, and financial stressors for Black adults with criminal justice contact in order to further our understanding of their depressive symptoms.